Comparative analysis of application of mobile operating system in coal mine - ZHANG Bing (Gong-kuang zidonghua, 2015)
Current main mobile operating systems such as Android, iOS and Windows were compared and analyzed from aspects of technology level, application cost and security, combined with specific technology requirements of mobile device used for coal mine enterprise, a conclusion was got that Android is the most suitable for application in ground and underground of coal mine, Windows is second to Android, and iOS can only be applied in ground.